Global synthesis reveals strong multifaceted effects of eucalypts on soils. Issue 8 (4th May 2022) - Mallen‐Cooper, Max; Atkinson, Joe; Xirocostas, Zoe A.; Wijas, Baptiste; Chiarenza, Giancarlo M.; Dadzie, Frederick A.; Eldridge, David J.
Abstract: Aim: Eucalypts have a widespread global distribution owing to their popularity for agroforestry and as environmental plantings. Despite an abundance of site‐specific evidence that eucalypts modify soils and soil processes, we lack a quantitative synthesis of their overall effects at the global scale. This limits our capacity to assess the likely impacts of future introductions in any given region of the world. Location: Global. Time period: 1986–2021. Major taxa studied: Eucalyptus, Angophora and Corymbia . Methods: We used a systematic search to derive a database of empirical data from 227 studies across 33 countries ( n effect size = 2, 806) and tested three predictions about the effects of eucalypts on soil properties and whether these effects varied with plantation age and soil depth. Results: Compared with (non‐eucalypt) native vegetation, eucalypts significantly reduced soil moisture, microbial abundance, nitrogen, cations and anions. Relative reductions in soil microbes and ions were stronger in older eucalypt plantations. A comparison of eucalypts with (non‐eucalypt) silvicultural and agropastoral systems revealed similar effects on most soil properties, although eucalypts tended to reduce potassium and enhance carbon to a greater extent than other managed systems. We found no consistent effects of eucalypts on soil pH. Main conclusions: Our study provides the first extensive global meta‐analysis of the effects of eucalypts on soil properties and processes and demonstrates that effects are highly dependent on the community with which they are compared (i.e., natural or managed). In general, our findings reinforce the widely held belief that eucalypts deplete soil nutrients and dominate water resources. Understanding how eucalypts affect soils allows us to assess their global suitability for agroforestry, soil rehabilitation and soil carbon enhancement, while considering the potential environmental costs.